2012
DOI: 10.3810/pgm.2012.07.2571
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Pharmacotherapy in 2012: Considerations in Medication Selection

Abstract: Diabetes is one of the most costly and burdensome chronic diseases, and its therapy and management have become increasingly complex. The incidence of type 2 diabetes mellitus (T2DM), a multiorgan disorder, is increasing at an epidemic rate in the United States and worldwide. Despite numerous scientific and medical advances, less than half of the population with T2DM has achieved the American Diabetes Association-recommended glycated hemoglobin level goal of < 7%, which is necessary to optimally manage the dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Blood glucose control is central to disease management, with target glycated hemoglobin (HbA 1c ) values personalized for individual patients, since the widely cited goal of HbA 1c <7.0% (53 mmol/mol) is not appropriate for all patients [2]. Even with less aggressive targets in many patients, the majority of patients with T2DM still fail to reach predefined therapeutic targets, despite the availability of many treatment options [3]. Coupled with this is evidence of clinical inertia in general practice, reflecting little improvement in achieving target HbA 1c goals in recent years, despite updated treatment guidelines recommending tight glycemic control [4].…”
Section: History Of Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood glucose control is central to disease management, with target glycated hemoglobin (HbA 1c ) values personalized for individual patients, since the widely cited goal of HbA 1c <7.0% (53 mmol/mol) is not appropriate for all patients [2]. Even with less aggressive targets in many patients, the majority of patients with T2DM still fail to reach predefined therapeutic targets, despite the availability of many treatment options [3]. Coupled with this is evidence of clinical inertia in general practice, reflecting little improvement in achieving target HbA 1c goals in recent years, despite updated treatment guidelines recommending tight glycemic control [4].…”
Section: History Of Conditionmentioning
confidence: 99%
“…DPP-4 inhibitors mainly target postprandial glucose (PPG) [3,13], whereas SGLT2 inhibitors have significant effects on FPG [14]. An analysis of the diurnal glycemic profiles of 290 patients with T2DM suggests that PPG and FPG contribute to raised HbA 1c levels to a different extent depending on the degree of hyperglycemia: at lower HbA 1c levels, PPG appeared to be the major contributor, whereas at HbA 1c levels >8.4% (>68 mmol/mol), FPG became dominant [15].…”
Section: Susan Cornell Bs Pharmd Cde Fapha Faadementioning
confidence: 99%
“…This situation may result in T2D depending on the frequency of the recurrent insult imposed on the body. It has been reported that skipping meals induces people to ingest more calories; 31% high-calorie food was consumed after short-term deprivation, a life-style increasingly common in society today [54]. It is estimated that 10-15% of T2D patients behave in this way.…”
Section: Sirt1 Variants and Diabetes Susceptibilitymentioning
confidence: 99%
“…Around the globe, there were 366 million diabetes patients in 2011, and it is estimated that there will be 552 million patients in 2030 [1]. Type 2 diabetes mellitus (T2DM) accounts for 90-95% of new-onset diabetes annually [2]. The development of T2DM is influenced by genetic components and environmental factors [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Thiazolidinediones (TZD) are insulin-sensitizing agents which could decrease fasting plasma glucose (FPG) and postprandial plasma glucose (PPG) levels by increasing glucose uptake in the peripheral tissue [2]. Pioglitazone is a new TZD, and the only available one which has been widely used for T2DM therapy [13,14].…”
Section: Introductionmentioning
confidence: 99%